Lessons Learned From a Pilot Project on Telemedicine Advance Care Planning in an Urban Geriatric Primary Care Office. (June 2022) - Seecof, Olivia M.; Allanoff, Molly; Liantonio, John; Parks, Susan
Purpose: There is a dearth of literature regarding the documentation of advance care planning (ACP) in the geriatric population, despite the controversial, yet well-studied need for ACP. The purpose of this pilot study was to provide an update to a prior study from our institution that outlined the need for increased documentation of advance care planning (ACP) in an urban geriatric population. Methods: Our study involved using telemedicine to conduct dedicated ACP visits and an electronic medical record (EMR) note-template specifically designed for these visits in an attempt to increase the amount of documented ACP in the EMR in this population. Results: The study did not yield significant results due to the inability to schedule enough patients for these dedicated visits. Discussion: While our study was ultimately unsuccessful, 3 crucial lessons were identified that will inform and fuel future interventions by the authors to further the study of documentation of ACP.